The effect of krill oil supplementation on skeletal muscle function and size in older adults: A randomised controlled trial. Issue 6 (June 2022) - Alkhedhairi, Saleh AA.; Aba Alkhayl, Faris F.; Ismail, Ahmad D.; Rozendaal, A.; German, M.; MacLean, B.; Johnston, L.; Miller, A.A.; Hunter, A.M.; Macgregor, L.J.; Combet, E.; Quinn, T.J.; et al.
Summary: Background & aims: The aim of this study was to determine the effect of krill oil supplementation, on muscle function and size in healthy older adults. Methods: Men and women, aged above 65 years, with a BMI less than 35kg/m2, who participated in less than 1h per week of structured self-reported exercise, were enrolled in the study (NCT04048096) between March 2018 and March 2020. Participants were randomised to either control or krill oil supplements (4g/day) for 6 months in this double blind randomised controlled trial. At baseline, 6 weeks and 6 months, knee extensor maximal torque was measured as the primary outcome of the study. Secondary outcomes measured were grip strength, vastus lateralis muscle thickness, short performance physical battery test, body fat, muscle mass, blood lipids, glucose, insulin, and C-Reactive Protein, neuromuscular (M-Wave, RMS and voluntary activation), and erythrocyte fatty acid composition. Results: A total of 102 men and women were enrolled in the study. Ninety-four participants (krill group (26 women and 23 men) and placebo group (27 women and 18 men)) completed the study (mean (SD): age 71.2 (5.1) years and weight 71.8 (12.3) kg). Six months supplementation with krill oil resulted in, an increase in knee extensor maximal torque, grip strength and vastus lateralis muscle thickness, relative to control (p<0.05). The 6-month treatment effects were 9.3% (95%CI: 2.8, 15.8%), 10.9% (95%CI: 8.3, 13.6%) and 3.5% (95%CI: 2.1, 4.9%) respectively. Increases in erythrocyte fatty acid profile were seen with krill oil for EPA 214% (95%CI: 166, 262%), DHA 36% (95%CI: 24, 48%) and the omega-3 index 61% (95%CI: 49, 73%), relative to control (p < 0.05). Krill oil resulted in an increased, relative to control (p < 0.05), M-Wave of 17% (95%CI: 12.7, 38.1%) but there was no effect of krill oil on RMS, voluntary activation, or on any other secondary outcomes such as performance of the short performance physical battery test or quality of life. Conclusion: Krill oil supplementation for 6 months results in statistically and clinically significant increases in muscle function and size in healthy older adults. ClinicalTrials.gov Identifier: NCT04048096.